Alimentação de leitões com dietas contendo soro de leite fermentado mais zinco e cobre orgânico - Hauschild, L. [UNESP]; Lovatto, P. A.; Lehnen, C. R.; Andretta, I.; Garcia, G.; Daniel, E. [UNESP] (SciELO Espana/Repisalud, 2012)
An experiment was carried out to evaluate the performance of piglets fed rations containing fermented milk and zinc and copper amino acid complex. Sixty four piglets, littermates, were used. The experimental design was based on random block with two dietary treatments. One of these contained a basal diet (DB) with ZnO e CuSO 4 and the other one with the DB, but without CuSO 4 and with the addition of fermented milk and zinc and copper amino acid complex (SLF Lact +ZnCuAA). There were eight replicate pens per treatment, and pigs were grouped at 4 per pen. The SLF Lact + ZnCuAA didn't not affect (p>0.05) final live weight of the piglets. However, live weight was different (p<0.01) between males and females (24.3 vs. 24.0 kg) at end of experiment. The feed intake of animals feed with SLF Lact+ZnCuAA was higher (p<0.01) in 8% in the first 14 days (0.261 vs. 0.239 kg/d), 15% from 15 to 28 days (0.756 vs. 0.675 kg/ d) and 12% from 29 to 42 days (1.091 vs. 0.962 kg/ d) compared to control group. Daily average feed intake in the experimental period was 11% higher (p<0.01) for the animals fed with the diet contained SLF Lact+ZnCuAA. Weight gain of the treatment with SLFL act+ZnCuAA was higher (p<0.01) by 14% from 0 to 14 days (0.176 vs. 0.152 kg/d), 11% from 15 to 28 days (0.564 vs. 0.500 kg/d) and 12% from 29 to 42 days (0,572 vs. 0,501 kg/d). Average daily weight gain of 42 days of trial of treatment with SLF Lact +ZnCuAA was 12% higher (p<0.01) compared to control group (0.437 vs. 0.384 kg/d). Feed conversion ratio was 8% lower (p<0.01) for treatment with SLF Lact+ZnCuAA in the first 14 days (1.487 vs. 1.614). Supplementation with fermented milk and zinc and copper amino acid complex in diets containing zinc oxide improved growth performance of weanling piglets.
Piglets feeding with diets containing milk fermented and zinc and copper organic
Keywords: Lactobacillus acidophilus; Metabolites; Microminerals; Pigs; Animalia; Suidae